The effectiveness of trading halts and investor trading performance - TAECHAPIROONTONG, Nareerat (Institutional Knowledge at Singapore Management University, 2012)
This paper examines the effectiveness of trading halts and the trading performance of different types of investors or traders during halts in an Asian emerging equity market. We use trade-by-trade data flagged by types of traders between January 1999 and December 2007. The results suggest that trading halts improve the efficiency of the market by reducing the information asymmetry and stabilizing the market. Trading halts serve as devices to facilitate a price discovery process by giving investors opportunity to adjust their trading interests and reaction to the material information. Our findings show that return and volatility tend to revert to their normal trading periods in a short period of time. High trading volume appears before and after halts but gradually decays within three days after resumption of trades. The results also reveal that long duration of halts may cause higher volatility than short duration ones. Moreover, the evidence shows that domestic investors trade at better prices than foreign investors around trading halt periods. Retail domestic investors trade at a more favourable price than institutional domestic and foreign investors. Retail investors seem to follow a contrarian trading strategy by buying low and selling high.